2022
DOI: 10.1038/s42003-022-03759-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric quantitative phase imaging for real-time, single cell, drug screening in breast cancer

Abstract: Quantitative phase imaging (QPI) measures the growth rate of individual cells by quantifying changes in mass versus time. Here, we use the breast cancer cell lines MCF-7, BT-474, and MDA-MB-231 to validate QPI as a multiparametric approach for determining response to single-agent therapies. Our method allows for rapid determination of drug sensitivity, cytotoxicity, heterogeneity, and time of response for up to 100,000 individual cells or small clusters in a single experiment. We find that QPI EC50 values are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…11 ) as well as previous characterization of commercial systems [26] , [27] , [28] , [29] . In previous work we have shown that measurements of cell mass and growth performed with a system based on these plans agree with commercial systems as well as independent measurements of cell growth [11] . Finally, the measured precision of ∼1–2 % is comparable to commercial systems [28] .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…11 ) as well as previous characterization of commercial systems [26] , [27] , [28] , [29] . In previous work we have shown that measurements of cell mass and growth performed with a system based on these plans agree with commercial systems as well as independent measurements of cell growth [11] . Finally, the measured precision of ∼1–2 % is comparable to commercial systems [28] .…”
Section: Discussionsupporting
confidence: 54%
“…When used alone or in addition to other imaging modalities, label free imaging techniques such as QPI offer opportunities to study live single cell attributes like mass accumulation, heterogeneity, and drug response [11] . QPI measures the phase shift as light passes through a transparent sample such as microbeads or live cells.…”
Section: Hardware In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rare drug-resistant diffuse large B cell lymphoma (DLBCL) cells within a population of DLBCL cells sensitive to a PI3-kinase inhibitor, idelalisib, were identifiable by continued mass accumulation and could, in concept, be isolated and recovered for further studies ,, Preclinical dry mass accumulation rate studies using patient derived xenografts predicted drug sensitivity for triple negative breast cancers, providing a potential QPI application for drug selection in personalized oncology , (Figure c). A separate drug screening in breast cancer study applied QPI to capture drug sensitivity that was consistent with findings from current standard approaches, as well as multiple additional physiologically relevant parameters that characterized cell responses to therapy . As discussed above, QPI measured viscoelasticity can differentiate between epithelial and mesenchymal states, a state transition that is a cardinal feature of cancer cell metastasis, and phase correlation imaging discriminated between quiescent and senescent cells, with potential implications for drug resistance and tumor reemergence …”
Section: Advances In Quantitative Biologymentioning
confidence: 66%
“…A separate drug screening in breast cancer study applied QPI to capture drug sensitivity that was consistent with findings from current standard approaches, as well as multiple additional physiologically relevant parameters that characterized cell responses to therapy. 256 As discussed above, QPI measured viscoelasticity can differentiate between epithelial and mesenchymal states, 250 a state transition that is a cardinal feature of cancer cell metastasis, and phase correlation imaging discriminated between quiescent and senescent cells, with potential implications for drug resistance and tumor reemergence. 230 QPI Morphological Applications in Diagnostics.…”
Section: Qpi Applications In Screening and Drug Sensitivity Measurementmentioning
confidence: 99%